Changes in microbial population in the rumen of sheep fed Acacia mearnsii tannin extract for methane reduction - Hassen, Abubeker (University of Pretoria, 2023)
Dissertation (MSc Agric Animal Science (Animal Nutrition))--University of Pretoria, 2023.